Exploring emerging water treatment technologies for the removal of microbial pathogens - Oluwatobi Victoria Obayomi; Damilare Cornelius Olawoyin; Olumide Oguntimehin; Lukman Shehu Mustapha; Samuel Oluwaseun Kolade; Peter Olusakin Oladoye; Seungdae Oh; Kehinde Shola Obayomi (Current Research in Biotechnology)
The availability of potable and clean water has become a global challenge. There are many variables that affect how equally people have access to clean water. Disparities are a result of inadequate infrastructure, which includes a deficiency of suitable pipelines, sanitation systems, and water treatment facilities. The presence of pathogenic microbes such as viruses, bacteria and protozoa in water has become a global public health concern. Pathogens present in water caused various disease outbreaks, health emergencies and increased cost of treatments. To address this challenge, a variety of methods for removing microbial pathogens from water sources have been developed and implemented. This review provides a thorough exploration of diverse methods utilized for pathogen removal in water treatment, encompassing physical, chemical, and biological approaches. It delves into the efficacy of each method, scrutinizing their constraints and practical implications. Furthermore, recent advancements and emerging technologies within the domain are explored, offering insights into potential future developments and enhancements. Future research efforts should focus on addressing these challenges to enhance the efficiency, reliability, and sustainability of water treatment systems for safeguarding public health and ensuring access to safe drinking water worldwide.